Dairy cow’s pastures quality in Jura Mountains and Comté cheese area: maintenance with draught horses - Mugnier S.; Bigot G.; Perret E.; Gaillard C.; Ingrand S. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
In PDO Comté cheese area, especially in the Jura Mountains, grass from pastures is the main feed of dairy cows during the grazing season. To maintain the high nutritive value of grass, farmers have to cut grass refusals after the exit of cows from the paddock. An alternative is to use horses to eat these grass refusals, thanks to complementary feeding behaviours between these 2 herbivorous species. Thus, some farmers associate draught horses to dairy cattle on pastures. The aim of our study is to analyse the farmers’ practices about grazing management when they associate horses and dairy cows on the same pastures. A survey was performed in 14 mixed (draught horses + dairy cattle) farms producing PDO Comté cheese. The results highlighted three types of associations between horses and lactating cows on pastures: (i) successive grazing, (ii) simultaneous grazing, (iii) winter grazing of horses. Moreover, three managements of grass refusals by cows were identified: (i) horses only, (ii) mowing only, (iii) both horses and mowing. In view of these 14 farms, the use of horse grazing to manage grass refusals could depend on the type of horse grazing, the equine stocking rate and the value of horses/cows ratio.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)